El estudio del paisaje como clave interpretativa del territorio a través de las narrativas para la planificación urbana y territorial : Paraty, Rio de Janeiro/Brasil como caso de estudio - Caron, Daniele (2017)
Contemporary territories are increasingly subject to tensions and contradictions resulting from the logic of capitalism. Urban and territorial planning, in turn, faces the challenge of interpreting these territories in order to organize their spaces and flows to make easier the collective and individual activities facilitate collective and individual activities and to improveme quality of life of its inhabitants. It is fundamental, then, to know how people interact with the territory, as well as their conflicts, demands and desires. This social and cultural perspective brings the planner’s views closer to the daily experience society. Landscape, as a phenomenon that relates subject and territory possesses a cultural dimension able to reveal the subjectivities of this everyday experience that acts as concrete imprint on the territory and as perception matrix. With the objective of developing a study of landscape from a phenomenological perspective we seek to build an analogy between the concepts of landscape and narrative, since both constitute cultural systems of signification developed from lived experience. We start from the hypothesis that narratives about the landscape of a given territory can contribute relevant and distinctive knowledge to urban and territorial planning. As study object we chose the exploration and investigation of narratives about landscape in the specific case of the Perequê-Açu river valley, in Paraty/Rio de Janeiro/Brasil, since this municipality presently constitutes a singular territory from the biophysical, sociocultural, urban and economic points of view. The need to preserve some identity values of this landscape requires a continuous conceptual and methodological exploration to create a cultural renewal capable of bringing the phenomenon closer to that place’s culture as well as to the diversity and to the increasing complexity of territorial processes. We looked into some examples in the northern western hemisphere and with more detail into examples in the Brazilian context, where the analyzed case is located. Then, we studied the analogy between the concepts of landscape and narrative looking for reflexive and operative keys for an interpretation of territory that incorporates the perception of subjects in its planning process. The study of the territorial matrixes of Paraty allowed the approach of a concrete reality for the research on landscape, and the verification that the aspects established on the theoretical framework were reflected therein. We achieved the methodology definition at the time we engaged the social networks and started to develop the ethnographical encounters with the landscape narrators. The narratives analysis was the most extensive process of the study. In them we developed a thorough contact with the accounts – fragmentation – in order to reveal the analysis units that allow for the creation of a relationship matrix between subjects and landscape – categorization.We then analyzed this matrix and formulated a cartographic and narrative metatext that expresses the essence of the subjects lived experience according to the themes of interest to the interpretation of territory for its planning. The elaboration of choreographies of the narrated landscape, which seek to express the way in which these investigated themes allow us to question the territory and lay out strategies to its planning, was made possible by the decoding of agglutinating arguments. Through the application of narratives discourse analysis methodology on landscape for this specific case study, we verified that: the implicit narrative themes of a particular social group contribute relevant knowledge to the landscape phenomenon ; that the narrated landscape choreography constitutes evidences of new strategies for the urban and territorial planning; and, finally, that the Perequê-Açu river hydrographic basin constitutes a fundamental axis for the municipality’s urban and territorial planning actions due to it’s being represented in the conservation and transformation processes of the landscape.